Estresse mental e metabólico em universitários - Woitchunas, William Gustavo (2020)
Stress affects individuals in different ways and at different stages of the life cycle. University students at different levels of maturity in academic development are often exposed to physical and emotional exhaustion, with subjective and hormonal responses that can trigger mental disorders and immunological diseases. Stress, when associated with circadian rhythm and antioxidant system disorders, implies premature aging. The main objective of the dissertation is to analyze the relationship between mental stress and metabolic stress in university students who attend class at different times of the day. The study that is part of the dissertation evaluates the metabolic (Cortisol and Lactate) and oxidative (TBARS and Glutathione) parameters in blood samples from students. The cross-sectional study included 48 university students from two undergraduate programs, one with daytime classes and the other with nighttime classes, from a university in the state of Santa Catarina (SC), Brazil. Participants answered a questionnaire that included sociodemographic questions and the Lipp's Stress Symptoms Inventory for Adults (LSSI). They also participated in laboratory analyzes, with blood samples containing EDTA and serum samples, obtained by venipuncture. The results of the study showed that the inferential statistical analyzes did not allow to confirm the link between the hormone cortisol and the time of the day, or between the symptoms of psychological stress and the biomarkers used. The daytime or nighttime class did not influence protein Thiols, but influenced non-protein Thiols and reduced glutathione (GSH), showing that nighttime students had a reduced antioxidant capacity. These findings indicate greater susceptibility to metabolic diseases and, consequently, premature aging. The research also highlights the important role of actions aimed at the well-being of university students, especially those who study at night.